Client and clinician-rated characteristics of problem gamblers with and without history of gambling-related illegal behaviors. (September 2018) - Ellis, Jennifer D.; Lister, Jamey J.; Struble, Cara A.; Cairncross, Molly; Carr, Meagan M.; Ledgerwood, David M.
Abstract: Individuals with gambling disorder are at an elevated risk for engaging in gambling-related illegal behaviors. The present study examined client ( N = 88) and clinician ratings ( N = 30) of client characteristics associated with a history of gambling-related illegal behaviors. We also examined client characteristics associated with history of arrest for a gambling-related crime. Gambling-related illegal behaviors and arrest were common (57.3% and 23.9%, respectively) in the present sample. Clients of younger age, and those with greater gambling-related financial consequences, lifetime alcohol problems, impulsivity, mood symptoms, and daily living role difficulties were more likely to report gambling-related illegal behaviors. Clients who had been arrested for a gambling-related crime were more likely to report daily living and role functioning difficulties and lifetime alcohol problems. Clinicians rated clients with a history of gambling-related illegal behaviors and/or gambling-related arrests as more impulsive, and clinicians also endorsed higher rates of treatment failure among these clients. Both client and clinician report suggested that clients with a history of illegal behaviors may have a variety of comorbid problems that may be a focus of clinical intervention. Highlights: Data for problem gamblers ( N = 88) and their clinicians ( N = 30) was analyzed in this study. 58.3% of the sample reported lifetime gambling-related illegal behaviors. 23.9% of the sample reported being arrested for gambling-related illegal behaviors. Gamblers with a history of illegal behaviors reported greater comorbid problems. Clinicians rated gamblers with a history of illegal behaviors as more impulsive.